31P magnetic resonance spectroscopy in skeletal muscle: Experts' consensus recommendations. (10th February 2020) - Meyerspeer, Martin; Boesch, Chris; Cameron, Donnie; Dezortová, Monika; Forbes, Sean C.; Heerschap, Arend; Jeneson, Jeroen A.L.; Kan, Hermien E.; Kent, Jane; Layec, Gwenaël; Prompers, Jeanine J.; Reyngoudt, Harmen; et al.
Abstract : Skeletal muscle phosphorus‐31 31 P MRS is the oldest MRS methodology to be applied to in vivo metabolic research. The technical requirements of 31 P MRS in skeletal muscle depend on the research question, and to assess those questions requires understanding both the relevant muscle physiology, and how 31 P MRS methods can probe it. Here we consider basic signal‐acquisition parameters related to radio frequency excitation, TR, TE, spectral resolution, shim and localisation. We make specific recommendations for studies of resting and exercising muscle, including magnetisation transfer, and for data processing. We summarise the metabolic information that can be quantitatively assessed with 31 P MRS, either measured directly or derived by calculations that depend on particular metabolic models, and we give advice on potential problems of interpretation. We give expected values and tolerable ranges for some measured quantities, and minimum requirements for reporting acquisition parameters and experimental results in publications. Reliable examination depends on a reproducible setup, standardised preconditioning of the subject, and careful control of potential difficulties, and we summarise some important considerations and potential confounders. Our recommendations include the quantification and standardisation of contraction intensity, and how best to account for heterogeneous muscle recruitment. We highlight some pitfalls in the assessment of mitochondrial function by analysis of phosphocreatine (PCr) recovery kinetics. Finally, we outline how complementary techniques (near‐infrared spectroscopy, arterial spin labelling, BOLD and various other MRI and 1 H MRS measurements) can help in the physiological/metabolic interpretation of 31 P MRS studies by providing information about blood flow and oxygen delivery/utilisation. Our recommendations will assist in achieving the fullest possible reliable picture of muscle physiology and pathophysiology. Abstract : 31 P MRS can usefully probe skeletal muscle cellular energy metabolism. Choice of methodology depends on the research question. The recommendations given here will help researchers experienced in general MRS with the application of 31 P MRS in skeletal muscle, covering the practicalities of data acquisition and muscle exercise as well as the physiological interpretation of the measurements. We also give expected values and tolerable ranges for some measured quantities, and minimum requirements for reporting results and acquisition parameters.